Analysis of Blended Learning Models Using Technology 4.0 to Improve Critical Thinking Skills - Mesterjon Mesterjon; Dwi Rulismi; Johanes Sapri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This study aims to measure the level of effectiveness of applying blended learning-based learning models by utilizing ICT technology (Technology 4.0) to improve students' critical thinking skills in normal news life while maintaining adaptation to the industrial revolution 4.0. This behavior has positioned students to carry out blended learning that is oriented towards the continuous use of technology 4.0. This new habit encourages students to have a competitive level of adaptation in the more complex era of the industrial revolution, and students must also have adaptations with technology to overcome problems that exist in the current era So the researchers made a concern to instill and strengthen the skills and abilities needed by students to face the Industrial Revolution 4.O era in the current era. In discussing this research, Critical thinking skills are selected as skills that are needed by every individual student today, because Critical thinking skills enable students to involve various aspects and tools needed in learning and through a systematic thinking process. Researchers are trying to find a method that is appropriate to the current era, namely blended learning. Blended learning which has been implemented by the educational institution where this research takes place is a collaborative learning method between conventional methods and modern methods (technology 4.O). This method is implemented by implementing several cycles and meeting parts. The methods used and those given in developing critical thinking are combining problem solving methods with video, blogging, YouTube and zoom meeting. Thus, students will learn something different and new in the implementation of their learning. This will spur students to think critically. Thus, students will have optimally developed critical thinking skills and students will be able to adapt quickly to the current era of the industrial revolution 4.0.